Tribo-electrochemical behaviour of 316L stainless steel: The effects of contact configuration, tangential speed, and wear mechanism - Salasi, Mobin; Stachowiak, Gwidon; Stachowiak, G. (Elsevier Ltd, 2015)
Tribo-electrochemical behaviour of 316L stainless steel was studied using three contact configurations: two-body ceramic counterface (2B-CC), three-body rubber counterface (3B-RC) and three-body ceramic counterface (3B-CC). Electrochemical methods were employed to investigate the effects of tangential speed and wear mechanism on the tribo-electrochemical characteristics of the 316L samples at each contact configuration. In both 2B-CC and 3B-RC contacts increasing the tangential speed resulted in higher current measured while in the 3B-CC contact the current was an increasing function of time even at a constant rotational speed. After the abrasion-corrosion tests different repassivation kinetics was found for each contact configuration.